SOSIALISASI DAMPAK PSIKOLOGIS, SOSIAL, DAN EKONOMI JUDI ONLINE: UPAYA PERLINDUNGAN GENERASI MUDA - Nursari, Ayu; Rahmawati, Hamida Nur; Pratama, Reza Hardian; Nurbaiti, Nurbaiti (MAJU : Indonesian Journal of Community Empowerment, 2025)
The development of digital technology has made it easier to access various forms of online entertainment, including online gambling, which is increasingly popular among the younger generation. This phenomenon raises serious concerns because of its broad impacts, including psychological, social, and economic aspects. Online gambling can cause addiction, mental health disorders, social dysfunction, and significant financial losses. Socialization regarding the negative impacts of online gambling is a strategic step in efforts to prevent and protect the younger generation from these dangers. This research and socialization program aims to increase public awareness, especially teenagers and parents, regarding the risks posed by online gambling. In addition, an educational and collaborative approach with various parties, such as educational institutions, government, and communities, is key to building the resilience of the younger generation against the negative influences of the digital world. By strengthening digital and mental literacy, it is hoped that the younger generation will be able to make wise decisions in using technology.